2006
DOI: 10.1177/00222194060390040901
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analyses of the Reading Development of Grade 4 Students with Reading Disabilities

Abstract: This study presents a longitudinal examination of the development of reading and reading-related skills of 22 Grade 4 children identified as having reading disabilities (RD) who had been followed since kindergarten. The analyses were conducted to investigate the patterns of emergence of RD as well as reading ability and risk status across the 5 years. The findings of the study are presented with an examination of the trajectories of the children with RD as compared to Grade 4 typical readers (matched for grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 33 publications
(42 reference statements)
8
102
2
Order By: Relevance
“…Most of the studies, however, have focused on the early phases of reading development or used relatively short follow-ups. The few studies that have followed reading development for several years have suggested that, although there is high stability in RD across grades at the group level (e.g., Compton, Fuchs, Fuchs, Elleman, & Gilbert, 2008;Landerl & Wimmer, 2008), there are-at least in English-also a considerable number of cases that move across the clinical threshold over time: children who are no longer affected (resolving RD; e.g., Catts, Compton, Tomblin, & Bridges, 2012) and children who do not develop RD until Grade 4 (late-emerging RD; e.g., Catts et al, 2012;Etmanskie, Partanen, & Siegel, in press;Leach, Scarborough, & Rescorla, 2003;Lipka, Lesaux, & Siegel, 2006).…”
Section: Late-emerging and Resolving Dyslexia: A Follow-up Study Frommentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies, however, have focused on the early phases of reading development or used relatively short follow-ups. The few studies that have followed reading development for several years have suggested that, although there is high stability in RD across grades at the group level (e.g., Compton, Fuchs, Fuchs, Elleman, & Gilbert, 2008;Landerl & Wimmer, 2008), there are-at least in English-also a considerable number of cases that move across the clinical threshold over time: children who are no longer affected (resolving RD; e.g., Catts, Compton, Tomblin, & Bridges, 2012) and children who do not develop RD until Grade 4 (late-emerging RD; e.g., Catts et al, 2012;Etmanskie, Partanen, & Siegel, in press;Leach, Scarborough, & Rescorla, 2003;Lipka, Lesaux, & Siegel, 2006).…”
Section: Late-emerging and Resolving Dyslexia: A Follow-up Study Frommentioning
confidence: 99%
“…Little research has been conducted on the characteristics of resolving and late-emerging RD, although the proportion of late-emerging cases has been reported to be approximately 40% of all RD cases in English (Catts et al, 2012;Leach et al, 2003;Lipka et al, 2006). The scarcity of information on these resolving and late-emerging RD groups presents challenges to early identification and prevention efforts of RD.…”
Section: Late-emerging and Resolving Dyslexia: A Follow-up Study Frommentioning
confidence: 99%
See 2 more Smart Citations
“…However, older students may have difficulty with reading for several reasons: (a) not all students are provided with substantive early intervention, (b) some students are provided with inadequate early intervention, (c) some students who are provided with effective intervention early struggle later when text and knowledge demands increase, and (d) some students manifest reading difficulties later in their schooling who did not have reading difficulties early (Leach, Scarborough, & Rescorla, 2003;Lipka, Lesaux, & Siegel, 2006). For these reasons, improved knowledge about effective interventions for older students is needed.…”
Section: Reading Interventions For Older Students With Reading Difficmentioning
confidence: 99%